Pengaruh Debt To Assets dan Deviden Policy terhadap nilai perusahaan pada Sector Goods Industry di Indonesia Stock Exchange Tahun 2017-2021 - Hulu, Wilhelmina; Tanjung, Ahmad Albar (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
One of the company's goals in general is to maximize the value of the company. The higher the company value, the higher the share price, and conversely the lower the company value, the lower the stock price. The purpose of this study is to analyze the influence of the Debt To Assets Ratio and Dividend Policy on the value of companies in the good industry sector. The research method used is a quantitative method. The data analysis technique used is multiple linear regression. The results of this study are that the Debt To Assets Ratio and Dividend Ratio have a significant influence on the firm value variable. The coefficient value of the determinant of the variable is 15.8%, which means that the Firm Value variable is not influential enough to explain the Debt To Assets Ratio and Dividend Policy variables. Based on the t test it is known that the results obtained are that Dividend Policy has a positive and significant effect on Firm Value, while the debt toll asset ratio has no positive and significant effect on Firm Value while Dividend Policy partially has quite an effect on Firm Value in the good industry sector in Indonesia.